Knowledge, assessment, and management of adults with joint hypermobility syndrome/Ehlers–Danlos syndrome hypermobility type among flemish physiotherapists. (March 2015) - Rombaut, Lies; Deane, Janet; Simmonds, Jane; De Wandele, Inge; De Paepe, Anne; Malfait, Fransiska; Calders, Patrick
Abstract : Physiotherapy plays a fundamental role in managing adults with the joint hypermobility syndrome/Ehlers–Danlos syndrome hypermobility type (JHS/EDS‐HT). However, it is a challenge for both the patient and the physiotherapist as the condition is poorly understood and treatment for JHS/EDS‐HT is currently undefined. Insight into current practice is, therefore, necessary in order to establish baseline knowledge in this area and in the long term to improve the standard of patient care. Therefore, the purpose of this study was to evaluate current physiotherapists' knowledge of JHS/EDS‐HT and to gain insight into current physiotherapy practice with emphasis on assessment, management, and treatment efficacy. Three hundred twenty‐five Flemish physiotherapists participated in the study by filling out electronically a modified version of the "Hypermobility and Hypermobility Syndrome Questionnaire" (HHQ), which covered theoretical constructs such as general knowledge, assessment, management, and learning in relation to generalized joint hypermobility and JHS/EDS‐HT. The results show that physiotherapists report a low level of confidence with regard to assessment and management of JHS/EDS‐HT. Knowledge of hypermobility and JHS/EDS‐HT is weak, especially regarding the features associated with JHS/EDS‐HT. Many treatment approaches are used by physiotherapists with the majority showing preference for education, reassurance, muscle strengthening, proprioceptive and core stability training. Almost all approaches were perceived as being clinically effective by the physiotherapists, highlighting a lack of consensus. In conclusion, this study in Flemish physiotherapists confirms that JHS/EDS‐HT is under‐recognized, not well known and deemed difficult to treat. Further education is required and sought by the physiotherapists surveyed, and future research is needed. © 2015 Wiley Periodicals, Inc.